GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 30 May 2020, 04:26 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  # If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f

Author Message
TAGS:

### Hide Tags

Math Expert V
Joined: 02 Sep 2009
Posts: 64243
If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f  [#permalink]

### Show Tags 00:00

Difficulty:   25% (medium)

Question Stats: 90% (02:05) correct 10% (03:32) wrong based on 20 sessions

### HideShow timer Statistics

If $$f(x) = \frac{5x+2}{3x−5}$$ and $$g(x) = x^2 – 2x – 1$$, then the value of $$g(f(f(3)))$$ is:

A. 1/3
B. 2/3
C. 1
D. 2
E. 6

_________________
Senior Manager  D
Joined: 12 Dec 2015
Posts: 495
Re: If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f  [#permalink]

### Show Tags

If $$f(x) = \frac{5x+2}{3x−5}$$ and $$g(x) = x^2 – 2x – 1$$, then the value of $$g(f(f(3)))$$ is:

A. 1/3
B. 2/3
C. 1
D. 2 --> correct: f(3)=$$\frac{5*3+2}{3*3−5}$$ = $$\frac{17}{4}$$, f(f(3))=f(17/4)=$$(5*(17/4)+2)/(3*(17/4)−5)$$ =$$\frac{85+8}{51−20}$$ =$$\frac{93}{31}$$ = 3, so g(f(f(3))) = g(f(17/4)) = g(3) = 3^2-2*3-1=9-6-1=2
E. 6
Senior Manager  G
Joined: 14 Oct 2019
Posts: 406
Location: India
GPA: 4
WE: Engineering (Energy and Utilities)
Re: If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f  [#permalink]

### Show Tags

f(x)=5x+2/3x−5 and g(x)=x2–2x–1
f(3)=(5*3+2)/(3*3−5) = 17/4
now, f(17/4) =(5*17/4+2)/(3*17/4−5) = 73/31 = 3
therefore, g(f(f(3))) = g(3) =3^2–2*3–1 = 2 Re: If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f   [#permalink] 02 Apr 2020, 10:22

# If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f  